Profil Minat Baca Siswa Sekolah Dasar dengan Menggunakan Aplikasi TikTok - Rismawati, Ismi; Noviyanti, Aisa Fahmi; Pujiyati, Anisa; Mahadini, Najwa; Sukardi, Rendi Restiana; Yuniarti, Yeni (Education and Development Research, 2023)
Abstract: Interest in reading can encourage a person to expand their knowledge. Reading is essential and significant in achieving educational success in various career fields. The need to foster interest in reading in elementary school students to become an asset in their lives. The TikTok application is widely used in all walks of life. This application is very influential in everyday people's lives. This study aims to determine the reading interest index of elementary school students with the TikTok application. This research method uses descriptive research. Data were collected using questionnaires, interviews, and observations in several elementary schools. The results of this study, namely, the pleasure of reading, reached 57.69 percent, while the pleasure of reading reached 53.23 percent. On the usefulness indicator of using TikTok, 47.43 percent did not agree that the TikTok application was proper. In contrast, on the motivational indicator of reading with TikTok, 49.57 percent said they disagreed that there was motivation to read on the TikTok application. The study results show that the reading interest index of elementary school students is in the medium category, and the TikTok application does not affect increasing students' reading interest. Abstrak: Minat baca dapat mendorong seseorang orang untuk memperluas ilmu pengetahuan. Membaca sangat diperlukan dalam kehidupan yang menjadi modal besar dalam mencapai kesuksesan pendidikan dengan karir berbagai bidang. Perlunya pemupukan minat baca pada siswa sekolah dasar untuk menjadi modal dalam kehidupannya. Aplikasi TikTok banyak digunakan di segala kalangan masyarakat. Aplikasi ini sangat berpengaruh dalam kehidupan masyarakat sehari-hari. Tujuan dari penelitian ini untuk mengetahui indeks minat baca siswa sekolah dasar dengan adanya aplikasi TikTok. Metode penelitian ini menggunakan penelitian deskriptif. Pengambilan data dilakukan dengan cara menggunakan angket, wawancara, serta observasi sekolah pada beberapa sekolah dasar. Hasil dari penelitian ini, yaitu indikator kesenangan membaca mencapai 57.69 persen, sedangkan kesenangan membaca mencapai 53.23 persen. Pada indikator kebermanfaatan penggunaan TikTok mencapai 47,43 persen tidak setuju aplikasi TikTok bermanfaat, sedangkan pada indikator motivasi membaca dengan TikTok mencapai 49, 57 persen menyatakan tidak setuju adanya motivasi minat membaca pada aplikasi TikTok. Maka dari hasil penelitian menunjukan indek minat baca siswa sekolah dasar pada kategori sedang, serta aplikasi TikTok tidak berpengaruh dalam peningkatan minat baca siswa.